Infiltration of M1, but not M2, macrophages is impaired after unilateral ureter obstruction in Nrf2-deficient mice - Sogawa, Yuji (Sci Rep, 2017)
Chronic inflammation can be a major driver of the failure of a variety of organs, including chronic kidney disease (CKD). The NLR family pyrin domain-containing 3 (NLRP3) inflammasome has been shown to play a pivotal role in inflammation in a mouse kidney disease model. Nuclear factor erythroid 2-related factor 2 (Nrf2), the master transcription factor for anti-oxidant responses, has also been implicated in inflammasome activation under physiological conditions. However, the mechanism underlying inflammasome activation in CKD remains elusive. Here, we show that the loss of Nrf2 suppresses fibrosis and inflammation in a unilateral ureter obstruction (UUO) model of CKD in mice. We consistently observed decreased expression of inflammation-related genes NLRP3 and IL-1β in Nrf2-deficient kidneys after UUO. Increased infiltration of M1, but not M2, macrophages appears to mediate the suppression of UUO-induced CKD symptoms. Furthermore, we found that activation of the NLRP3 inflammasome is attenuated in Nrf2-deficient bone marrow–derived macrophages. These results demonstrate that Nrf2-related inflammasome activation can promote CKD symptoms via infiltration of M1 macrophages. Thus, we have identified the Nrf2 pathway as a promising therapeutic target for CKD.